Analysis of The Influence of Market Share of Islamic Commercial Banks in Indonesia: Microeconomic and Macroeconomic Indicators - Puspita Sari, Anggi (Tasharruf : Journal of Islamic Economics and Business, 2023)
The intention of this study is to examine how macroeconomic factors, microeconomic indicators, the NPF Nett ratio, and Third Party Funds (DPK) affect the growth of the market share of Islamic commercial banks in Indonesia from 2016 to 2023. The Financial Services Authority's Islamic Banking Statistics statistics are available on the official website www.ojk.go.id, which is the study's information source. One of the criteria utilized in this study is Islamic Commercial Banks that have constantly been registered with the Financial Services Authority (OJK) between 2016 and 2023. In this study, data are processed and Classical Assumptions are tested using the Least Square (LS) method. Research of this kind is quantitative. The results of this study indicate that the macroeconomic indicators are the inflation and interest rate variables, FDR, ROA, BOPO, and NPF Nett statistically have no influence, but implies that the NOM, CAR, and DPK variables statistically have influence on the market share of Islamic Commercial Banks in Indonesia in the period 2016-2023.